2013
DOI: 10.3846/13923730.2013.782335
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Concrete Containing Crumb Rubber

Abstract: Every year, colossal amounts of used and non-biodegradable rubber tyres are accumulated in the world. Experience shows that the most efficient way to increase the concrete fracture energy G F (N/m) is to use metal or polypropylene fibres. The optimal content of fibre increases concrete resistance to stress (especially tensile stress under bending force). Concrete fracture is not brittle; concrete continues deforming after maximum stresses and is able to resist certain stresses, there is no abrupt decrease in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Normally the conventional concrete is strong in compression but less resistance against tension, toughness and fatigue. The resistance against these properties can be enhanced by the inclusion of high strain capacity materials in concrete and is a most appropriate option . Under different kinds of loading the fibers are more influential in enriching the toughness and ductility of the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Normally the conventional concrete is strong in compression but less resistance against tension, toughness and fatigue. The resistance against these properties can be enhanced by the inclusion of high strain capacity materials in concrete and is a most appropriate option . Under different kinds of loading the fibers are more influential in enriching the toughness and ductility of the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…By examining mixture RC (the controlled one) to RCB3 (15Cr), the compressive strength for cubes dropped from 8.2 % to 16.5% at crumb rubber percentage, which varies from 10% to 15% by replacement of sand, respectively. Several studies have previously reported the decline in compressive strength subjected to rubber contents by revealing the negative effect [6,14,17,18]. The nature of the crumb hydrophobic allowed to increase the voids by air in the concrete mixtures and lead to concentrate the stress across micro cracks that caused by rubber thereby reduction in hardness strength [19].…”
Section: Flexure Test Setup Instrumentation and Loading Proceduresmentioning
confidence: 99%
“…Using the same approach and greater rubber volumes, Khaloo et al [12] fabricated rubberized concrete test specimens at percentages of 12.5%, 25%, 37.5%, and 50% and subjected them to uniaxial compression tests with controlled deformation, which exhibited significant reductions in the strength and elasticity modulus and an important reduction in the concrete brittle behaviour when the rubber content was increased. These researchers and others [13][14][15] studied the energy dissipation in concrete by means of the three points' beam geometry. In the present research work the Disk-Shaped Compact Tension test normed by the ASTM D7313-13 standard [16] is adopted to evaluate the fracture energy of concrete mixes.…”
Section: Experimental Studiesmentioning
confidence: 99%